Empowerment of Farm Families in Cross River State, Nigeria - F.M., Onu; I.B., Ubua; R.L., Ubua (Journal of Home Economics Research, 2024)
The paper examined the challenges which face the farm families in agricultural production and suggested mechanisms for empowering the farm families to improve their agricultural productivity. Many factors hider the progress of farmers in food production which include adaptation to climate change issues like flooding, high rate of inflation, high cost of farm inputs, insecurity and corruption challenges. Unfortunately, many farmers find it difficult to grapple with the problems of food insecurity caused by some obvious challenges. The farmers therefore need to be empowered to enable them solve the problem of food production especially in Cross River state where flooding, insecurity of lives and other challenges make farmers not to do their best in food production. The paper therefore examined some factors which affect the farm families in agricultural production and ways of empowering the farmers to improve agricultural productivity in Cross River state, Nigeria. Conclusions were reached that the problem of food insecurity could be addressed if the farmers are empowered and obstacles that hinder the farmers’ food production removed. Based on the conclusions, some recommendations were made; one of which is that farmers should be encouraged to form association-based co-operatives on their value chain and geographical location to enable them channel their problems collectively as a group for easy recognition by the government and her agencies.